BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Mammal assemblage composition predicts global patterns in emerging infectious disease risk - Yingying X. G. Wang; Kevin D. Matson; Luca Santini; Piero Visconti; Jelle P. Hilbers; Mark A. J. Huijbregts; Yanjie Xu; Herbert H. T. Prins; Toph Allen; Zheng Y. X. Huang; Willem F. de Boer (Global Change Biology, 2021)
As a source of emerging infectious diseases, wildlife assemblages (and related spatial patterns) must be quantitatively assessed to help identify high‐risk locations. Previous assessments have largely focussed on the distributions of individual species; however, transmission dynamics are expected to depend on assemblage composition. Moreover, disease–diversity relationships have mainly been studied in the context of species loss, but assemblage composition and disease risk (e.g. infection prevalence in wildlife assemblages) can change without extinction. Based on the predicted distributions and abundances of 4466 mammal species, we estimated global patterns of disease risk through the calculation of the community‐level basic reproductive ratio R0, an index of invasion potential, persistence, and maximum prevalence of a pathogen in a wildlife assemblage. For density‐dependent diseases, we found that, in addition to tropical areas which are commonly viewed as infectious disease hotspots, northern temperate latitudes included high‐risk areas. We also forecasted the effects of climate change and habitat loss from 2015 to 2035. Over this period, many local assemblages showed no net loss of species richness, but the assemblage composition (i.e. the mix of species and their abundances) changed considerably. Simultaneously, most areas experienced a decreased risk of density‐dependent diseases but an increased risk of frequency‐dependent diseases. We further explored the factors driving these changes in disease risk. Our results suggest that biodiversity and changes therein jointly influence disease risk. Understanding these changes and their drivers and ultimately identifying emerging infectious disease hotspots can help health officials prioritize resource distribution.

Genetic diversity, structure, and patterns of differentiation in the genus Vitis - M. Aradhya; Y. Wang; M. A. Walker; B. H. Prins; A. M. Koehmstedt; D. Velasco; J. M. Gerrath; G. S. Dangl; J. E. Preece (Plant Systematics and Evolution, 2013)

Global lack of flyway structure in a cosmopolitan bird revealed by a genome wide survey of single nucleotide polymorphisms - Robert H. S. Kraus; Pim van Hooft; Hendrik‐Jan Megens; Arseny Tsvey; Sergei Y. Fokin; Ronald C. Ydenberg; Herbert H. T. Prins (Molecular Ecology, 2013)
Knowledge about population structure and connectivity of waterfowl species, especially mallards ( A nas platyrhynchos ), is a priority because of recent outbreaks of avian influenza. Ringing studies that trace large‐scale movement patterns have to date been unable to detect clearly delineated mallard populations. We employed 363 single nucleotide polymorphism markers in combination with population genetics and phylogeographical approaches to conduct a population genomic test of panmixia in 801 mallards from 45 locations worldwide. Basic population genetic and phylogenetic methods suggest no or very little population structure on continental scales. Nor could individual‐based structuring algorithms discern geographical structuring. Model‐based coalescent analyses for testing models of population structure pointed to strong genetic connectivity among the world's mallard population. These diverse approaches all support the conclusion that there is a lack of clear population structure, suggesting that the world's mallards, perhaps with minor exceptions, form a single large, mainly interbreeding population.

Restoring native forest ecosystems after exotic tree plantation in Madagascar: combination of the local ectotrophic species Leptolena bojeriana and Uapaca bojeri mitigates the negative influence of the exotic species Eucalyptus camaldulensis and Pinus patula - R. Baohanta; J. Thioulouse; H. Ramanankierana; Y. Prin; R. Rasolomampianina; E. Baudoin; N. Rakotoarimanga; A. Galiana; H. Randriambanona; M. Lebrun; R. Duponnois (Biological Invasions, 2012)

Seedling resistance to stem rust race Ug99 and marker analysis for Sr2, Sr24 and Sr31 in South African wheat cultivars and lines - Z. A. Pretorius; Y. Jin; C. M. Bender; L. Herselman; R. Prins (Euphytica, 2012)

Rhizosphere microbiota interfers with plant-plant interactions - A. Sanon; Z. N. Andrianjaka; Y. Prin; R. Bally; J. Thioulouse; G. Comte; R. Duponnois (Plant and Soil, 2009)

Rhizosphere microbiota interfers with plant-plant interactions - A. Sanon; Z. N. Andrianjaka; Y. Prin; R. Bally; J. Thioulouse; G. Comte; R. Duponnois (Plant and Soil, 2009)

Responses of Pinus halepensis growth, soil microbial catabolic functions and phosphate-solubilizing bacteria after rock phosphate amendment and ectomycorrhizal inoculation - L. Ouahmane; J. C. Revel; M. Hafidi; J. Thioulouse; Y. Prin; A. Galiana; B. Dreyfus; R. Duponnois (Plant and Soil, 2009)

Responses of soil microbial catabolic diversity to arbuscular mycorrhizal inoculation and soil disinfection - A. P. Dabire; V. Hien; M. Kisa; A. Bilgo; K. S. Sangare; C. Plenchette; A. Galiana; Y. Prin; R. Duponnois (Mycorrhiza, 2007)

Arbuscular mycorrhizal colonization and nodulation improve flooding tolerance in Pterocarpus officinalis Jacq. seedlings - L. Fougnies; S. Renciot; F. Muller; C. Plenchette; Y. Prin; S. M. de Faria; J. M. Bouvet; S. Nd. Sylla; B. Dreyfus; A. M. Bâ (Mycorrhiza, 2007)

The ectomycorrhizal fungus Scleroderma bermudense alleviates salt stress in seagrape (Coccoloba uvifera L.) seedlings - E. Bandou; F. Lebailly; F. Muller; M. Dulormne; A. Toribio; J. Chabrol; R. Courtecuisse; C. Plenchette; Y. Prin; R. Duponnois; M. Thiao; S. Sylla; et al. (Mycorrhiza, 2006)

Contrasting responses to ectomycorrhizal inoculation in seedlings of six tropical African tree species - A. G. Diédhiou; O. Guèye; M. Diabaté; Y. Prin; R. Duponnois; B. Dreyfus; A. M. Bâ (Mycorrhiza, 2005)

Ectomycorrhizal symbiosis enhanced the efficiency of inoculation with two Bradyrhizobium strains and Acacia holosericea growth - S. André; A. Galiana; C. Le Roux; Y Prin; M. Neyra; R. Duponnois (Mycorrhiza, 2005)

Nucleotide sequence analyses of genomic RNAs of Peanut stunt virus Mi, the type strain representative of a novel PSV subgroup from China - L. Y. Yan; Z. Y. Xu; R. Goldbach; C. Kunrong; M. Prins (Archives of Virology, 2005)

The last common ancestor of Sarcolaenaceae and Asian dipterocarp trees was ectomycorrhizal before the India–Madagascar separation, about 88 million years ago - M. Ducousso; G. Béna; C. Bourgeois; B. Buyck; G. Eyssartier; M. Vincelette; R. Rabevohitra; L. Randrihasipara; B. Dreyfus; Y. Prin (Molecular Ecology, 2004)
Phylogenetic studies comparing the Dipterocarpaceae and the Sarcolaenaceae, a tree family endemic to Madagascar, have shown that the Sarcolaenaceae share a common ancestor with Asian dipterocarps. This suggests that Asian dipterocarps drifted away from Madagascar with the India–Seychelles landmass and then dispersed through Asia. Although all dipterocarps examined so far have been found to be ectomycorrhizal, the ectomycorrhizal status of Sarcolaenaceae had not been investigated. Here we establish the ectomycorrhizal status of Sarcolaenaceae using histological and molecular methods. This indicates that the common ancestor of the Sarcolaenaceae and Asian dipterocarps was ectomycorrhizal, at least before the separation of the Madagascar–India landmass, 88 million years ago.

Molecular tracing of Bradyrhizobium strains helps to correctly interpret Acacia mangium response to inoculation in a reforestation experiment in Madagascar - Y. Prin; A. Galiana; C. Le Roux; B. Méléard; V. Razafimaharo; M. Ducousso; G. Chaix (Biology and Fertility of Soils, 2003)

High sequence conservation among cucumber mosaic virus isolates from Lily - Y. K. Chen; A. F. L. M. Derks; S. Langeveld; R. Goldbach; M. Prins (Archives of Virology, 2001)

Improvement of nitrogen fixation in Acacia mangium through inoculation with rhizobium - A. Galiana; G. M. Gnahoua; J. Chaumont; D. Lesueur; Y. Prin; B. Mallet (Agroforestry Systems, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)